BEHAVIORAL STRATEGIES OF THE PERSONNEL IN THE CROSS-CULTURAL INTERACTION PROCESS AS A PRECONDITION OF EFFECTIVE DEVELOPMENT OF THE ENTERPRISE: UKRAINE AND MONGOLIA - T. P. Blyznyuk (Фінансово-кредитна діяльність: проблеми теорії та практики)
This article deals with the results of the study to determine, compare and analyze the behavioral strategies of personnel of Ukrainian and Mongolian enterprises in the process of cross-cultural interaction. The aim of this study is to identify, compare and analyze behavioral strategies of the personnel that are typical of representatives of Ukrainian and Mongolian enterprises in the process of cross-cultural interaction as a precondition for the effective development of the enterprise. To determine the behavioral strategy of personnel in the process of cross-cultural interaction, a methodical approach based on the questionnaire “Types of ethnic identity” was used. As a result of the research it was revealed that the personnel of Ukrainian enterprises adhere to the behavioral strategy of “intermediaries”, and the personnel of Mongolian enterprises adhere to three different categories of behavioral strategies (“intermediaries”, “nationalists” and “ethnophobia’s neurotics”). As a result of the study, it was determined that the personnel of the studied Ukrainian enterprises in comparison with the personnel of the Mongolian enterprises have a more positive ethnic identity that indicates readiness for cross-cultural interaction. The personnel of Ukrainian enterprises only require additional information about the culture of the representatives of which they will be interacting. While only part of Mongolian personnel (60%) is ready for cross-cultural interaction and has an appropriate behavioral strategy, 35% of personnel is not ready for cross-cultural interaction, and 5% of personnel has not yet determined their behavioral strategy in the process of cross-cultural interaction. It means that the personnel of the studied Mongolian enterprises require to carry out additional training and training in the context of cross-cultural management in order to increase the ethnic identity and bring it to a positive level, since almost half of the personnel is not ready to carry out the process of cross-cultural interaction. The results of the research can become one of the key aspects for the development of practical recommendations for the strategy of effective development of these enterprises, taking into account the peculiarities of personnel behavior in the process of cross-cultural interaction.